Efektivitas Senam Dismenore terhadap Intensitas Nyeri Menstruasi dan Tingkat Kecemasan pada Remaja Putri - A’ida Fitriana Putri; Siti Mudlikah (Universitas Muhammadiyah Gresik, 2026)
Background: Dysmenorrhea is one of the most common reproductive health problems among adolescent girls and may interfere with daily activities, learning concentration, and psychological well-being. Non-pharmacological interventions such as dysmenorrhea exercise are considered effective in reducing menstrual pain and anxiety. Objective: This study aimed to determine the effect of dysmenorrhea exercise on reducing menstrual pain and anxiety among adolescent girls at MTs Al-Hidayah Wedoro. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The population consisted of 53 female students in grades VII and VIII at MTs Al-Hidayah Wedoro. A total of 15 respondents who experienced dysmenorrhea and met the inclusion criteria were selected using purposive sampling. The intervention consisted of dysmenorrhea exercise performed regularly during one menstrual cycle. Menstrual pain intensity was measured using the Numeric Rating Scale (NRS), while anxiety levels were assessed using the Generalized Anxiety Disorder-7 (GAD-7) questionnaire. Data were analyzed using paired t-test with a significance level of 0.05. Results: The mean menstrual pain score decreased from 8.12 before intervention to 6.20 after intervention. The mean anxiety score decreased from 16.52 to 5.16 after intervention. Paired t-test analysis showed significant differences in menstrual pain (p=0.000) and anxiety levels (p=0.001) before and after dysmenorrhea exercise. Conclusion: Dysmenorrhea exercise is effective in reducing menstrual pain and anxiety levels among adolescent girls. Therefore, dysmenorrhea exercise can be recommended as a non-pharmacological intervention for adolescent reproductive health programs.